Modelling errors calculation adapted to rainfall – Runoff model user expectations and discharge data uncertainties. (April 2017) - Douinot, Audrey; Roux, Hélène; Dartus, Denis
Abstract: A novel objective function for rainfall-runoff model calibration, named Discharge Envelop Catching (DEC), is proposed. DEC meets the objectives of: i) taking into account uncertainty of discharge observations, ii) enabling the end-user to define an acceptable uncertainty, that best fits his needs, for each part of the simulated hydrograph. A calibration methodology based on DEC is demonstrated on MARINE, an existing hydrological model dedicated to flash floods. Calibration results of state-of-the-art objective functions are benchmarked against the proposed objective function. The demonstration highlights the usefulness of the DEC objective function in identifying the strengths and weaknesses of a model in reproducing hydrological processes. These results emphasize the added value of considering uncertainty of discharge observations during calibration and of refining the measure of model error according to the objectives of the hydrological model. Highlights: A novel objective function taking into account discharge observations uncertainty, model specifics and user-defined tolerance. A resulting calibration methodology is demonstrated on an existing hydrological model dedicated to flash floods. The results of state-of-the-art objective functions are benchmarked against the proposed objective function.